2006
DOI: 10.1163/156854006777584269
|View full text |Cite
|
Sign up to set email alerts
|

Gonad and androgenic gland development in relation to sexual morphology in Pandalopsis japonica Balss, 1914 (Decapoda, Pandalidae)

Abstract: This paper describes the role of the androgenic gland (AG) in the reproductive phase change from male to female in the protandrous hermaphroditic shrimp, Pandalopsis japonica. The differentiation of external sexual characters is presented in relation to the development of the hermaphroditic gonad and the AG. Juveniles ( 11 mm carapace length (CL)) externally exhibit male morphological characters, but do not show differentiated testicular tissue internally. Sexually functional males (14-23 mm CL) have both sper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Chiba et al 2000, Onishi et al 2001. Kim et al (2006) confirmed protandrous sex change of Pandalopsis japonica by histological observation. Protandrous hermaphroditism is also suggested for P. coccinata, P. glabra and P. pacifica, although they are not listed in Table 1 (T. Komai, personal communication).…”
Section: Hermaphroditsm In Decapod Crustaceansmentioning
confidence: 55%
“…Chiba et al 2000, Onishi et al 2001. Kim et al (2006) confirmed protandrous sex change of Pandalopsis japonica by histological observation. Protandrous hermaphroditism is also suggested for P. coccinata, P. glabra and P. pacifica, although they are not listed in Table 1 (T. Komai, personal communication).…”
Section: Hermaphroditsm In Decapod Crustaceansmentioning
confidence: 55%
“…Individual maturation was determined using the GSI, as described in Kim et al (2006). The expression of both Pj-Vg1 and Pj-Vg2 transcripts was at a basal level in the hepatopancreas and ovary of immature individuals (GSI 0.2-1.3).…”
Section: Expression Analysismentioning
confidence: 99%
“…To date, research about the shrimp has focused on the development of the larva (Komai & Mizushima, 1993;Komai, 1999), the energy budget of the larva (Kim et al, 2013), sperm structure (Kim et al, 2003(Kim et al, , 2006 and genetic studies Salma et al, 2012). For the active management and maintenance fisheries, juvenile shrimp must be grown and released.…”
Section: Introductionmentioning
confidence: 99%